EFEKTIFITAS FUNGSI PENGAWASAN PANITIA PENGAWAS PEMILU KOTA PEKANBARU DALAM PELAKSANAAN PEMILU ANGGOTA DPR, DPD DAN DPRD TAHUN 2014 BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2012 - Ferdy Aryona Putra; Emilda Firdaus; Maxasai indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The occurance of elections in Indonesia is held directly, thus, supervising the ececution of the election is required. As set out in Constitution Act number 15 of 2011 (Undang-Undang No.15 Tahun 2011), Election Supervisory Committee has duties , powers and obligations in the conduct of elections . In the 2014 legislative elections helt in the city of Pekanbaru , some form of violation occurred, for instance, administrative offense , criminal offense , violation of code of conduct , and those are not a violation of the election instead. Based on this conception , the writing of this thesis generates three formulation of the problem , whic are : First , how is the function of supervising the Election Supervisory Committee ( Panwaslu ) of Pekanbaru city in carrying out the task of monitoring the election of members of DPR , DPD and DPRD 2014 by Constitution Act number 8 of 2012 (Undang-Undang No. 8 Tahun 2012)? Secondly , What are the obstacles regarding the Election Supervisory Committee ( Panwaslu ) in the implementation's monitoring of election of members of DPR, DPD and DPRD in Pekanbaru city? The research method in this study start with first, the type of research is sociological and descriptive . Secondly, the research site of Election Supervisory Committee of Pekanbaru city. The source of data is supported by the primary, secondary, and tertiary data sources. Thirdly, the data agregation methods used are interviews , and a review of literature. After the data are collected and undergo qualitative analysis, then the sum up of conclusions is done within deductive thinking method, which is by analyzing problems from general into specific form Based on the conduction of the research, there are three main issues that can be concluded , first , the supervision function Election Supervisory Committee ( Panwaslu ) of Pekanbaru city in carrying out the task of monitoring the election of members of DPR , DPD and DPRD 2014 by Constitution Act number 8 of 2012 (Undang-Undang No. 8 Tahun 2012) has not gone properly and not in maximum effort, because the presence of obstacles experienced by the Election Supervisory Committee . Secondly, the barriers faced by the Election Supervisory Committee ( Panwaslu ) in supervising the implementation of the legislative elections in the city of Pekanbaru include the factor of human resources, recruitment and formation factor of Election Supervisory Committee, and also geographical conditions .Keywords : Function - Election Supervisory Committee - Pekanbaru